Alternative control of phytopatogens - Moraes, Walkvria B. C. (Pesquisa Agropecuaria Brasileira, 1992)
Plants, like animals and men, are subject to temporary or permanent protection from the attack of such phytopathogenical microorganisms as viruses, bacteria and fungi. Experience has shown that such temporary protection or even immunization, which is permanent, occurs when the plant has its defense mechanisms activated through treatments with saprophytic microoganism or antivirus breeds of a given pathogen, or even of a attenuated or dead pathogen. Pathogenic organisms or their metabolytes can also induce resistance in plants of varying intensity, longevity and scope in accordance with the microorganisms used as inductors and depending on environmental conditions, plant age and tissue treated, etcetera. In Brazil, laboratory and field experiments have shown the feasibility of the use of induction methods for resistance in several crops such as cereals, coffee, bananas and others. Main interest in the use of alternative control is concentrated on the possibility of plant immunization. This means control which will last throughout the whole life cycle of the host plant. Mainly, in the case of perennial crops, the use of immunization has been shown to be possible, usable and efficient.